Angular anisotropy of prompt γ rays and fragment spin alignment in binary and light-charged-particle-accompanied spontaneous fission of 252Cf - Kopach, Yu. N.; Singer, P.; Mutterer, M.; Klemens, M.; Hotzel, Arthur; Schwalm, Dirk; Thirolf, P.; Hesse, M.; Gönnenwein, F. (Physical review letters, 1999)
Angular correlations of prompt γ rays in binary and light-charged-particle (LCP)-accompanied spontaneous fission of 252Cf were measured with a 4π-crystal-ball NaI(Tl) γ-ray spectrometer. For 3H, 4He, 6He, Li, and Be accompanied fission, γ-ray angular distributions were deduced with respect to the motion both of the fragments and the LCPs. There is no indication for a change of the fragment spin alignment by the LCP release or for a correlation between the LCP direction and a bending motion at scission, as was argued in previous investigations. Consequences for the understanding of fragment spin formation are briefly discussed.
Im Titel ist "252" hochgestellt
Gesehen am 30.11.2020